The Synthesis Methodology of PEGylated Fe3O4@Ag Nanoparticles Supported by Their Physicochemical Evaluation - Magdalena Kędzierska; Piotr Potemski; Anna Drabczyk; Sonia Kudłacik-Kramarczyk; Magdalena Głąb; Beata Grabowska; Dariusz Mierzwiński; Bożena Tyliszczak (Molecules, 2021)
Many investigations are currently being performed to develop the effective synthesis methodology of magnetic nanoparticles with appropriately functionalized surfaces. Here, the novelty of the presented work involves the preparation of nano-sized PEGylated Fe3O4@Ag particles, i.e., the main purpose was the synthesis of magnetic nanoparticles with a functionalized surface. Firstly, Fe3O4 particles were prepared via the Massart process. Next, Ag+ reduction was conducted in the presence of Fe3O4 particles to form a nanosilver coating. The reaction was performed with arabic gum as a stabilizing agent. Sound energy-using sonication was applied to disintegrate the particles’ agglomerates. Next, the PEGylation process aimed at the formation of a coating on the particles’ surface using PEG (poly(ethylene glycol)) has been performed. It was proved that the arabic gum limited the agglomeration of nanoparticles, which was probably caused by the steric effect caused by the branched compounds from the stabilizer that adsorbed on the surface of nanoparticles. This effect was also enhanced by the electrostatic repulsions. The process of sonication caused the disintegration of aggregates. Formation of iron (II, III) oxide with a cubic structure was proved by diffraction peaks. Formation of a nanosilver coating on the Fe3O4 nanoparticles was confirmed by diffraction peaks with 2θ values 38.15° and 44.35°. PEG coating on the particles’ surface was proven via FT-IR (Fourier Transform Infrared Spectroscopy) analysis. Obtained PEG–nanosilver-coated Fe3O4 nanoparticles may find applications as carriers for targeted drug delivery using an external magnetic field.